MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SMK MELALUI PENDEKATAN PROBLEM-BASED LEARNING - Retno Minarty Rahayu; Martin Bernard (IKIP Siliwangi, 2022)
Online learning during the pandemic makes students less understanding of mathematical concepts so that student learning outcomes decrease when learning is again carried out face-to-face. Therefore we need an approach that is able to make students understand mathematical concepts through meaningful experiences without depending on the teacher. Then the problem-based learning approach was chosen and carried out by means of group discussions.The research method used in this study is Classroom Action Research conducted through three cycles whose cycle has 1 meeting. The subject of this research are 10 students of class XI TKRO 1 of SMK Karya Bhakti Pusdikpal Cimahi. The data was collected by using a test and then analyzed using percentage techniques with a limit of 85% reached the lower achievement criteria which is 75. The results showed that mathematics learning, could improve student mathematics learning outcome. The average value of the final test given in each cycle has increased. The average value of the final test of mathematics learning outcomes for student in cycle I was 75,6; in cycle II was 82, and in cycle III was 85,3. So it can be concluded that the use of the Problem-Based Learning approach can improve student learning outcomes.